Systematic Survey of the Alteration of the Faecal Microbiota in Rats With Gastrointestinal Disorder and Modulation by Multicomponent Drugs - Wu, Yue; Wu, Yang; Wu, Hongwei; Wu, Changxun; Ji, Enhui; Xu, Jing; Zhang, Yi; Wei, Junying; Zhao, Yi; Yang, Hongjun (Frontiers in Pharmacology, 2021)
Functional dyspepsia (FD) is a widespread functional gastrointestinal disorder. Disorders in the intestinal flora have been found in FD patients. However, the interaction between FD and the intestinal flora has not been studied comprehensively. In addition, multicomponent drugs represented by traditional Chinese medicine (TCM) are widely used for treating FD, but their modulation of the intestinal flora has not been investigated. Therefore, in this study, a high-throughput sequencing strategy was used to investigate alterations in the intestinal flora in a rat FD model, followed by an investigation of the modulation by a representative TCM, Xiaoerfupi (XEFP) granule. The results showed that in rats with FD, the relative abundances of Erysipelotrichaceae, Lactobacillaceae, Streptococcaceae increased and that of Ruminococcaceae decreased. At the macro level, the levels of LysoPC(16:0), LysoPC(20:2(11Z,14Z)), LysoPC(15:0), LysoPC(20:2(11Z,14Z)), LysoPC(20:1(11Z)), LysoPC(15:0), LysoPC(20:0) and LysoPE(0:0/20:0) in serum increased and levels of PC(16:1(9Z)/20:3(8Z,11Z,14Z), PC(18:2(9Z,12Z)/20:2(11Z,14Z)), PC(o-16:0/20:4(8Z,11Z,14Z,17Z)), PE(MonoMe(13,5)/MonoMe(11,5)) decreased. The imbalance of metabolites was restored by XEFP through ether lipid metabolism pathway. Increase in the phyla Firmicutes/Bacteroidetes (F/B) ratio of the FD rats was restored by XEFP as well. Moreover, XEFP can relief the symptoms of FD rats by increasing beneficial bacteria Ruminococcaceae and decreasing harmful Streptococcaceae, Erysipelotrichaceae and Lactobacillaceae This study represents a comprehensive survey of the interaction between FD and the intestinal flora and a systematic evaluation of modulation by a multicomponent drug.